Organ Trafficking Crime in Indonesia: How is it Implemented and Regulated According to International Law? - Selviana, Nana; Kinanti, Fatma Muthia; Bangun, Budi Hermawan; Arsensius, Arsensius (Uti Possidetis: Journal of International Law, 2024)
This research discusses the implementation of the United Nations Convention against Transnational Organized Crime regarding organ trafficking in Indonesia by adopting a normative juridical approach to analyse international legal instruments, particularly UNTOC, and Indonesia's national legal regulations following the ratification of UNTOC by Indonesia, including the Indonesian Criminal Code, the Human Trafficking Law, and the Health Law. This research observes primary, secondary, and tertiary data sources. The research findings indicate that UNTOC is applicable to eradicate human organ trafficking in Indonesia. However, its implementation in Indonesia still faces challenges, particularly in the scope of law enforcement and public awareness. This study emphasises the importance of human rights protection, careful clinical evaluation, and transparency in reporting data related to organ transplantation. Moreover, this study suggests to increase international cooperation, strengthen law enforcement, victim protection, and to enhance public awareness to combat the wrongful act of organ trafficking. Also, national regulations and public education must be strengthened to improve the efforts against transnational organized crime.